Managing Volunteers: Constructing the Identity of Shop Managers in Charity Retailing - Ling, Yujia (2016)
This dissertation examines how identities construction of charity shop managers are accomplished through social discourse. It is based on a study of a paid charity shop manager and volunteers in a local charity retail shop in the UK - a specialized shop within a national charitable organization. It contributes empirically and theoretically to the literature of manager-volunteer communication. Drawing on techniques of discourse analysis, the dissertation presents detailed interpretation of a rich database. In this process, by examining the dynamics of manager-volunteer interaction the identity of the charity shop manager is socially constituted, negotiated, shaped and reshaped. In addition to primary data, based on a number of publications, a discourse among a charity shop manager and volunteers is conceptualized as a discourse of instruction, a discourse of training and a discourse of social talk. Three types of discourse provide contexts where power and politeness are played out by charity shop managers and volunteers. Understanding how the dynamics of their interaction progress, it is better to tackle a common issue of volunteer shortage in the charity retailing sector.